Studies on Seed Germination, Bud Activation And Early Budshoot Growrh of Hevea Brasiliensis (Muell. Arg.) - Alcala, Eugenio A. (1991)
The reduction of uneven early growth of Hevea buddings which could overcome the problem of low percentage of tappable trees during the early years of tapping was evaluated. The investigation covered a series of studies on the germination of Hevea seeds; bud activation of budded stumps to induce early bud-break by using growth regulators, other techniques and other growth regulating materials; and the manipulation of early growth of Hevea budshoot after emergence. An anatomical study on the budpatch under the various bud activation treatments was also carried out.